1997
DOI: 10.1615/critreveukargeneexpr.v7.i3.40
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Clotting Factors

Abstract: Blood clotting involves a multitude of proteins that act in concert in response to vascular injury to produce the procoagulant enzyme alpha-thrombin, which in turn is responsible for the generation of the fibrin plug. However, while generation of the fibrin plug is required for the arrest of excessive bleeding, unregulated clotting will result in the occlusion of the blood vessels and thrombosis. Thus, the regulation of the delicate balance between the procoagulant and anticoagulant mechanisms is of extreme im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
100
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 0 publications
1
100
0
Order By: Relevance
“…The prothrombinase complex, which is composed of the nonenzymatic cofactor factor Va, the enzyme, factor Xa, and the substrate, prothrombin, associated on a cell membrane-surface in the presence of Ca 2ϩ ions, is responsible for ␣-thrombin formation during blood coagulation (1,2). The prothrombinase complex catalyzes the activation of prothrombin ϳ300,000 times more efficiently than factor Xa alone (3).…”
mentioning
confidence: 99%
“…The prothrombinase complex, which is composed of the nonenzymatic cofactor factor Va, the enzyme, factor Xa, and the substrate, prothrombin, associated on a cell membrane-surface in the presence of Ca 2ϩ ions, is responsible for ␣-thrombin formation during blood coagulation (1,2). The prothrombinase complex catalyzes the activation of prothrombin ϳ300,000 times more efficiently than factor Xa alone (3).…”
mentioning
confidence: 99%
“…The prothrombinase complex responsible for the generation of ␣-thrombin in the hemostatic process is composed of factor Va and factor Xa associated on a phospholipid membrane in the presence of Ca 2ϩ (1,2). Although factor Xa alone can convert prothrombin to ␣-thrombin, the prothrombinase complex has a catalytic efficiency five orders of magnitude greater than factor Xa acting alone (3).…”
mentioning
confidence: 99%
“…Thrombin, factor Xa, and the RVV-factor V activator can produce factor Va by discrete proteolytic cleavages (for details see reviews (1,2)). It has also been reported that a protease from the venom of Naja naja oxiana produces a factor Va-like molecule lacking a major portion of the carboxyl terminal domain of the heavy chain, with diminished cofactor activity (46).…”
mentioning
confidence: 99%
“…It is clear that the catalytic specificities of blood coagulation proteases are supported by the carboxyl-terminal half of the enzymes, a trypsin-like serine protease domain (20). The prime role of the serine protease domain has also been demonstrated in the interaction of the blood coagulation proteases with their cofactors.…”
mentioning
confidence: 99%